Processes of suburbanization in the agglomeration of Rzeszow and Rzeszow Metropolitan Area during the crisis - Łuków, Agnieszka (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2015)
The economic crisis implies a lot of the processes taking place in the economy by slowing economic, social, cultural and limits entrepreneurial attitudes. The crisis also has an impact on the rapid decline in the economic activity, manifests in disruption in financial fluidity, the reduction of production, employment and investment activities,tas well as the financial resources of companies and people. The crisis affects the change in the rate of development of regional and national structures. The author tries to indicate the selected socio-economic problems and the effects of the functioning of Rzeszow city and its surroundings in the face of crisis. The aim is to show in the socio - economic and demographic the changes affecting the suburbanization processes in the agglomeration of Rzeszow and Rzeszow Metropolitan Area. The time horizon of the study includes the period of 1995-2012 - the period of the economic crisis of recent years. The subject of the analysis is the issue of population growth (population dynamics, natural motion, net migration) and the impact of the crisis on the suburbanisation of the agglomeration of Rzeszow.